Estimates of Caffeine Use Disorder, Caffeine Withdrawal, Harm and Help-seeking in New Zealand: A cross-sectional survey. (October 2020) - Booth, N.; Saxton, J.; Rodda, S.N.
Highlights: One in five daily caffeine consumers exceed the recommended 400 mg daily limit. 85% of respondents report at least one caffeine-related harm in the past year. 20% of respondents met DSM-5 criteria for CUD, and 30% for caffeine withdrawal. Medium and high (vs low) caffeine use tripled the odds of CUD. Women and smokers may be more prone to CUD and withdrawal than men and non-smokers. Abstract: Background: Caffeine Use Disorder (CUD) is not yet formally recognized in the DSM-5, but emerging evidence suggests CUD could impact up to one in five people. The primary aim of this study was to estimate levels of caffeine consumption and its associations with CUD and withdrawal, taking socio-demographic characteristics (age, gender, ethnicity, income) into account. Secondary aims were to measure caffeine-related harm and treatment preferences. Methods: We administered an online cross-sectional survey via Facebook to a convenience sample of 2379 adults in New Zealand. Caffeine consumption was assessed across six products: coffee, tea, energy drinks, cola, alcohol mixed with caffeine, and other products (e.g., caffeine pills, sports supplements). Results: 20% of participants met proposed criteria for CUD, with 30% meeting DSM-5 criteria for caffeine withdrawal. Moderate (200–400 mg per day) and high consumption (>400 mg per day) was associated with a three-fold increase in the odds of CUD and a two-fold increase in the odds of withdrawal. Women and current smokers were at higher risk of CUD and withdrawal even at moderate consumption levels. Nearly 85% of respondents experienced at least one caffeine-related harm in the past 12-months. The number of harms increased with level of caffeine consumption. Nearly 50% indicated a self-help treatment for caffeine reduction would be of interest. Conclusions: High rates of CUD and caffeine withdrawal amongst moderate caffeine users, women and smokers suggests caffeine consumption guidelines may need refinement. Caffeine-related harm that is not clinically meaningful may still be of concern to individuals and warrants further investigation.